Trends in ixodid tick abundance and distribution in Great Britain. - Scharlemann, J; Johnson, P; Smith, A; Macdonald, D; Randolph, SE (2008)
The popular, but rarely documented, view in Britain is that ticks have increased in distribution and abundance over recent years. To assess this, we gathered evidence for changes in tick distribution and abundance by distributing a survey questionnaire throughout Britain and by analysing trends in the prevalence of tick infestation on red grouse chicks Lagopus lagopus scoticus Latham (Galliformes: Tetranoidae), gathered over 19 years at three Scottish sites, and on deer (Cetartiodactyla: Cervidae) culled over 11 years on 26 Ministry of Defence (MoD) estates. Based on the survey, the current known distribution of Ixodes ricinus Linnaeus (Acari: Ixodidae) has expanded by 17% in comparison with the previously known distribution. The survey indicated that people perceive there to be more ticks today than in the past at 73% of locations throughout Britain. Reported increases in tick numbers coincided spatially with perceived increases in deer numbers. At locations where both tick and deer numbers were reported to have increased, these perceived changes occurred at similar times, raising the possibility of a causal link. At other locations, tick numbers were perceived to have increased despite reported declines in deer numbers. The perceptions revealed by the survey were corroborated by quantitative data from red grouse chicks and culled deer. Tick infestation prevalence increased over time on all grouse moors and 77% of MoD estates and decreased at six locations.